Aspectos sintáticos das estruturas relativas restritivas em português - Wang, Chunyuan (2020)
The Master’s thesis aims to propose a new analysis of non-movement, namely, the non-movement head external analysis, for the derivation of the restrictive relative structures in Portuguese based on the MP model of Generative Grammar, specifically, the Phase model, in order to solve the existing problems in the previous studies. In summary, there are five syntactic properties in the relative structures in Portuguese, namely, (1) the fundamental structure of which is right-adjunction [NP CP]; (2) there is no movement involved in the derivational process; (3) the base empty category is subcategorized; (4) the “que” element is a C complementizer; (5) the relative pronoun is generated at the base in the Spec-CP position. There are three theoretical advantages in this research, which are: (1) it is more economical; (2) it strictly respects the movement restrictions of Ross (1967) and Chomsky (1977); (3) a unified mechanism is obtained to dynamically derive all restrictive relative structures in Portuguese. In organization, this research follows four main guiding questions and is divided into three Chapters. The questions are: (1). What is the look of the MP model in relation to Kayne's LCA (1994)? (2) Is the fundamental structure [DP D CP] supported by the promotion model for relativization adequate? (3) Is relativization in Portuguese the result of movement or non-movement? (4) Is there a base empty category for relativization in Portuguese? What is its syntactic property? In this thesis, Chapter 1 raises a theoretical review of the three existing models for the derivation of relative structures, namely, the traditional model, the promotion model and the matching model. Chapter 2 makes a review of existing studies for the derivation of relative structures in Portuguese and the discussion of the aspects involved. And Chapter 3 presents the computational syntactic mechanism and the central concepts of the Phase model and is dedicated to the derivation of relative structures in Portuguese.